Imaginative Teaching through Creative Writing: A Guide for Secondary Classrooms - Amy Ash, Michael Dean Clark, Chris Drew (Bloomsbury Publishing, 2021)
Growing out of recent pedagogical developments in creative writing studies and perceived barriers to teaching the subject in secondary education schools, this book creates conversations between secondary and post-secondary teachers aimed at introducing and improving creative writing instruction in teaching curricula for young people. Challenging assumptions and lore regarding the teaching of creative writing, this book examines new and engaging techniques for infusing creative writing into all types of language arts instruction, offering inclusive and pedagogically sound alternatives that consider the needs of a diverse range of students. With careful attention given to creative writing within current standards-based educational systems, Imaginative Teaching through Creative Writing confronts and offers solutions to the perceived difficulty of teaching the subject in such environments. Divided into two sections, section one sees post-secondary instructors address pedagogical techniques and concerns such as workshop, revision, and assessment before section two explores hands-on activities and practical approaches to instruction. Focusing on an invaluable and underrepresented area of creative writing studies, this book begins a much-needed conversation about the future of creative writing instruction at all levels and the benefits of collaboration across the secondary/post-secondary divide.